KDANet: optical recognition for Bangla language using deep neural networks - Rabbi, Kazi Kamruzzaman; Dev, Pranto; Hossain, Akram; Sadman, Aninda (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.